AlScN/GaN HEMTs with 4 A/mm on-current and maximum oscillation frequency >130 GHz - Kazuki Nomoto; Joseph Casamento; Thai-Son Nguyen; Lei Li; Hyunjea Lee; Chandrashekhar Savant; Austin Lee Hickman; Takuya Maeda; Jimy Encomendero; Ved Gund; Timothy Vasen; Shamima Afroz; et al. (Applied Physics Express)
Aluminum Scandium Nitride (AlScN) is an attractive material for use as a lattice-matched epitaxial barrier layer in GaN high-electron mobility transistors (HEMTs). Here we report the device fabrication, direct current (DC) and radio frequency (RF) characteristics of epitaxial AlScN/AlN/GaN HEMTs on SiC substrates with regrown ohmic contacts. These devices show record high on-current of over 4 A/mm, high cutoff frequency ( f _T ) of 92.4 GHz and maximum oscillation frequency ( ${f}_{{\rm{MAX}}}$ ) of 134.3 GHz.